Differences in social responsibility toward youth - A case study based comparison of cooperatives and corporations - Marja-Leena Ruostesaari; Eliisa Troberg (Elsevier BV, 2022)
This study examines companies' responsibility for young people from the Corporate Social Responsibility (CSR) point of view. We compare cooperatives with listed companies in regard to responsibility for young people. Much research has been carried out about CSR, but comparative studies about the CSR programs of listed companies and cooperatives concerning young generation are lacking. In addition, CSR studies rarely discuss the relationship between an organization and the young generation.
The theoretical framework consists of literature of CSR including stakeholder theory and cooperative values and principles. The study uses qualitative comparative case study design. We examined why, how and to what extent listed companies and customer- owned cooperatives take responsibility for young people as well as how can companies' youth responsibility be seen in their CSR strategy and stakeholder discussions. The major research focus is: Are there differences in the companies' responsibility actions due to different ownership and stakeholder structures? The findings indicate that cooperatives engage more in youth collaboration than listed companies do. The main reasons for this are the cooperatives' local ownership and stakeholder structure and value-based operations. (C) 2016 Published by Elsevier Ltd.